N6-methyladenosine methylation analysis of circRNAs in acquired middle ear cholesteatoma - He, Jun; Mahmoudi, Ahmad; Yao, Jacqueline; Yuan, Qiulin; Fu, Jinfeng; Liu, Wei (Frontiers in Genetics, 2024)
Introduction: Middle ear cholesteatoma is a chronic middle ear disease characterized by severe hearing loss and adjacent bone erosion, resulting in numerous complications. This study sought to identify pathways involved in N6-methyladenosine (m6A) modification of circRNA in middle ear cholesteatoma. Methods: A m6A circRNA epitranscriptomic microarray analysis was performed in middle ear cholesteatoma tissues (n=5) and normal post-auricular skin samples (n=5). Bioinformatics analyses subsequently explored the biological functions (Gene Ontology, GO) and signaling pathways (Kyoto Encyclopedia of Genes and Genomes, KEGG) underlying middle ear cholesteatoma pathogenesis. Methylated RNA immunoprecipitation qPCR (MeRIP-qPCR) was performed to verify the presence of circRNAs with m6A modifications in middle ear cholesteatoma and normal skin samples. Results: Microarray analysis identified 3755 circRNAs as significantly differentially modified by m6A methylation in middle ear cholesteatoma compared with the normal post-auricular skin. Among these, 3742 were hypermethylated (FC≥3, p<0.05) and 13 were hypomethylated (FC≤1/3, p<0.05). GO analysis terms with the highest enrichment score were localization, cytoplasm, and ATP-dependent activity for biological processes, cellular components, and molecular functions respectively. Of the eight hypermethylated circRNA pathways, RNA degradation pathway has the highest enrichment score. Peroxisome Proliferator-Activated Receptor (PPAR) signaling pathway was hypomethylated. To validate the microarray analysis, we conducted MeRIP-qPCR to assess the methylation levels of five specific m6A-modified circRNAs: hsa_circRNA_061554, hsa_circRNA_001454, hsa_circRNA_031526, hsa_circRNA_100833, and hsa_circRNA_022382. The validation was highly consistent with the findings from the microarray analysis. Conclusion: Our study firstly presents m6A modification patterns of circRNAs in middle ear cholesteatoma. This finding suggests a direction for circRNA m6A modification research in the etiology of cholesteatoma and provides potential therapeutic targets for the treatment of middle ear cholesteatoma.